Artificial Intelligence Enabled Human Resource Management: A Review and Future Research Avenues - Chowdhury, Shah Ridwan; Guha, Souman; Sanju, Nehad Laila (Archives of Business Research, 2024)
This paper investigates the emergent issues of Artificial intelligence intervention in redefining the HR processes. Grounded on the Technology, Organization, and Environment (TOE) theory of Information system and Job-Demand-Resource (JDR) theory of HRM, this paper investigates AI intervention in HRM to find out how HRM functions are getting redefined in the future workplace by reviewing 70 research papers in this field which were selected and screened by using the Prisma Flow diagram. These papers were categorized into different themes and sub-themes based on HR functions including, recruitment, performance management, compensation management, employee relations, and ethical concerns for stakeholders associated with those functions. This paper highlights the ethical concerns and challenges of AI and proposes solutions to develop effective practices to embed AI within organizational frameworks. Findings of this paper elucidates on embedding AI-related HR technology in existing business intelligence system of organizations with a redefined focus of HR functions to ensure employees privacy concerns are properly ensured, relevant data are extracted and utilized having informed consent from the stakeholders and organizational justice is not overshadowed in performance and compensation management in the process of Algorithm based rigid assessment. This paper synthesizes the adverse effects of AI in HRM and demonstrates mitigating principles to tackle the perils of AI. Since there exists little theoretical development and empirical evidence involving AI‘s role in HRM, this paper provides new avenues of interdisciplinary researches to connect diffusion of AI in workplace with HRM theories and investigate predictive capabilities and design mechanisms of AI in HRM functions.